ANALISIS BUKU AQIDAH AKHLAK KELAS V MADRASAH IBTIDAIYAH AL-ZAYTUN BERDASARKAN PSIKOLOGI PERKEMBANGAN ANAK - Sudi Hermanto; Henri Peranginangin (JOEL: Journal of Educational and Language Research, 2023)
The purpose of writing this thesis is to describe the content of the material, the moral values ​​that are to be instilled in students, the structure of the presentation of the material from the point of view of developmental psychology, and to describe how the development of Aqidah Akhlak material leads to effective learning goals. The research method in writing this thesis is broken down into five items. First, the type of research used, namely using theoretical research and descriptive presentation. Second, data collection techniques, using documentation or literature techniques. Third, data sources, which in this study use textual media or literature. Fourth, data analysis techniques, which use inductive analysis. And, fifth, checking the validity of the data, which in this study was carried out by clearly listing the object or data source, both in the body notes and in the bibliography. The research results or analysis results, as the core part of this thesis, are presented in the third chapter, namely Discussion of Problem Formulation. This chapter describes the content of the material in the Aqidah Akhlak textbook for class V Madrasah Ibtidaiyah Al Zaytun, the moral values ​​contained therein, how the material is presented from a developmental psychology perspective, and how the material is developed so that it leads to effective learning. This thesis ends with a closing chapter which contains conclusions and suggestions. In the Conclusion sub-chapter, the results of the analysis of the fifth grade Aqidah Akhlak textbook at Madrasah Ibtidaiyah Al Zaytun are presented, namely that the fifth grade Aqidah Akhlak textbook at Madrasah Ibtidaiyah Al Zaytun contains subjects that support children's moral development. In addition, language development, social development, emotion, and cognitive development of children are also stimulated by their growth and development through the presentation of material in each chapter.